2007
DOI: 10.1038/sj.ejcn.1602964
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y polymorphism significantly magnifies diabetes and cardiovascular disease risk in obesity: the Hoorn Study

Abstract: The leucine7 to proline7 (Leu7Pro) polymorphism in preproneuropeptide Y (preproNPY) has been associated with accelerated atherosclerosis and type II diabetes, both of which are obesity-related diseases. The current study evaluated the impact of obesity on the disease risk linked to the Leu7Pro polymorphism of preproNPY in 393 elderly subjects. In 6 years follow-up, the polymorphism alone did not change the risk for abnormal glucose regulation, while obesity was associated with a significant 3-fold risk (odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Interestingly, these tendencies occurred without major differences in WAT depot weights or at the level of hepatosteatosis in the OE-NPY DBH male mice. This suggests that increased NPY may have a diabetogenic effect in the context of obesity and supports the association of the L7P polymorphism with an earlier onset of diabetes in the obese human population [14]. …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, these tendencies occurred without major differences in WAT depot weights or at the level of hepatosteatosis in the OE-NPY DBH male mice. This suggests that increased NPY may have a diabetogenic effect in the context of obesity and supports the association of the L7P polymorphism with an earlier onset of diabetes in the obese human population [14]. …”
Section: Discussionsupporting
confidence: 72%
“…The NPY 1228T > C polymorphism (rs16139), which causes an amino acid substitution of Leucine 7 to Proline 7 (L7P) in the signal peptide [9] is functional, enhancing the secretion of NPY [10, 11]. It is associated with an earlier onset of type 2 diabetes in carriers of L7P [12], as well as with other traits of the metabolic syndrome [13] especially in obese subjects [14]. Recently, it was reported that there is a gender difference in the NPY-mediated effects of the Proline 7 allele [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the L7P polymorphism is associated with IGT and an earlier onset of type 2 diabetes in carriers of p.L7P,[7879] especially in obese subjects. [80] Again the OE-NPY DBH mice display with similar phenotype: IGT associated with obesity. Recently, it was reported that there is a gender difference in the NPY-mediated effects of the P7 allele.…”
Section: Clinical Relevancementioning
confidence: 99%
“…As of 1 January 2009, a total of 27 candidate genes for obesity from the hypothalamic pathways have been examined (see overview in Table S1), including 21 genes reported to be associated with obesity‐related phenotypes in the last HOGM update (24). Since November 2005, new studies on 11 of these 21 genes have been published, showing that variants in the following genes are associated with the risk of obesity: AGRP (25,26), BDNF (27–29), GAD2 (30), HTR2A (31,32), LEPR (33–40), MC4R (42–53,56), NPY (54–56), NPY2R (57–60), POMC (61,62) and UBL5 (63) (Table S1). However, in addition to these positive studies, a few other studies were unable to reproduce the associations between genetic markers in AGRP (54), BDNF (26), GAD2 (64,65), LEPR (41,66–68), MC3R (49), MC4R (69–71), NPY (57,72) and NPY2R (73) with obesity‐related phenotypes.…”
Section: Association Studies In Genes In the Hypothalamic Pathwaysmentioning
confidence: 99%